Sports Injury Surveillance Systems and Guidelines in Japan: A Systematic Review - Mashimo, Sonoko; Ogaki, Ryo; Suhara, Hirokazu; Yoshida, Naruto (International Journal of Sports Medicine, 2022)
This systematic review aimed to identify sports injury surveillance systems (ISSs) and injury surveillance guidelines (ISGs) developed and currently used in Japan. Additionally, the extent to which ISSs and ISGs developed overseas are employed in Japan was also examined. A systematic search of electronic databases was performed in March 2021. Prospective studies that investigated sports injuries and targeted Japanese athletes or sports in Japan were included to identify the following: (1) details of the ISSs or ISGs developed among sports in Japan, and (2) characteristics of studies focusing on sports in Japan employing ISSs or ISGs developed overseas and the method of use. A total of five ISSs developed among sports in Japan were included, most of which were based on insurance benefits or condolence payment systems. In total, 23 studies used ISSs or ISGs developed overseas, more than half of which were used as a resource for the development of other data collection tools or methods, indicating that the definition of injury and/or classification of items are modified based on the needs among sports in Japan. This review highlights the necessity of establishing club-based or organisational ISSs and ISGs that are appropriate for sports in Japan.
Keywords: sports injury surveillance system; sports injury surveillance guideline; epidemiology; japanese athletes